The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/bf03327470
|View full text |Cite
|
Sign up to set email alerts
|

Binge eating in surgical weight-loss treatments. Long-term associations with weight loss, health related quality of life (HRQL), and psychopathology

Abstract: Objective Previous studies that have investigated the relationship between binge eating and the long-term outcome of bariatric surgery have shown mixed results. Does binge eating before or after bariatric surgery affect long-term BMI, health-related quality of life (HRQL), or psychopathology after surgery? The objective of the present study was to address these questions to determine the extent to which binge eating needs to be addressed in the context of bariatric surgery Methods. We assessed 173 bariatric pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Of the 11 studies that evaluated the relationship between post-operative binge eating and weight loss, eight studies documented significant associations between poorer weight loss outcomes and binge eating [23-28], LOC, or uncontrolled eating [26, 29, 30]. Two studies reported non-significant relationships between binge eating and weight loss [31, 32]. One study was unable to evaluate for an association because binge eating was not endorsed by any patients after surgery [33].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 11 studies that evaluated the relationship between post-operative binge eating and weight loss, eight studies documented significant associations between poorer weight loss outcomes and binge eating [23-28], LOC, or uncontrolled eating [26, 29, 30]. Two studies reported non-significant relationships between binge eating and weight loss [31, 32]. One study was unable to evaluate for an association because binge eating was not endorsed by any patients after surgery [33].…”
Section: Resultsmentioning
confidence: 99%
“…The fact that there are no data providing information on binge eating disorder can be seen as a major limitation of the present study, considering that binge eating is known to be highly prevalent among obese individuals [26] and bariatric surgery candidates both pre- and post-surgery [30]. Binge eating disorder in turn is associated with higher rates of psychological impairment such as depression [42] and with markedly affected HrQoL [43], thus making its assessment and consideration even more relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high prevalence of affective disorders [4, 10, 29] as well as non-normative eating behaviors and binge eating (disorder) among obese individuals [26, 27] and in particular among bariatric surgery candidates [10, 3033], each of which is known to be associated with difficulties in ER, further research in this respect is required. With the help of new findings, psychological interventions focusing on ER could be implemented and specifically adapted to meet the needs of obese individuals [34, 35], supporting patients both before and after bariatric surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, the adult WLS experience also suggests potential links between these pre-operative psychological comorbid conditions and/or their persistence or post-operative recurrence with poorer weight loss as well as HRQOL outcomes. (4143) Thus, adolescent symptom profiles should be closely monitored and referrals provided accordingly to optimize patient outcomes.…”
Section: Discussionmentioning
confidence: 99%